1993
DOI: 10.1017/s0020818300028009
|View full text |Cite
|
Sign up to set email alerts
|

Side-payments versus security cards: domestic bargaining tactics in international economic negotiations

Abstract: The literature on international economic cooperation has devoted relatively little attention to domestic bargaining tactics and their determinants. Recent scholarship has tended to stress the utility and frequency of side-payments while discounting other prominent bargaining tactics and a broader understanding of tactical choice. This article argues that policymakers choose among domestic bargaining tactics to garner support when faced with situations in which other government officials or societal interest gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…This fits the concessions that the Danes received in the renegotiation over the Treaty in December 1992. Empirical work to corroborate these points are beyond the scope of this article, but it is clear that the models of this article suggest some interesting questions for empirical research in this area (Evans, Jacobson and Putnam, 1993;Friman, 1993;Lehman and McCoy, 1992;Schoppa, 1993).…”
Section: Discussionmentioning
confidence: 85%
“…This fits the concessions that the Danes received in the renegotiation over the Treaty in December 1992. Empirical work to corroborate these points are beyond the scope of this article, but it is clear that the models of this article suggest some interesting questions for empirical research in this area (Evans, Jacobson and Putnam, 1993;Friman, 1993;Lehman and McCoy, 1992;Schoppa, 1993).…”
Section: Discussionmentioning
confidence: 85%
“…In the electoral sphere, economic groups may influence election results by financing campaigns of candidates with whom they are politically aligned. This means that, even before election, candidates rely on the funds raised to finance their According to Friman (1993), this is required to "combine emotional appeals to patriotic duty and self-sacrifice with arguments that incorporate widely held beliefs on the nature of basic challenges to those core values" (FRIMAN, 1993, p. 392 Fordham and McKeown (2003), the advantage of a geographic concentration is the cohesion and coordination of economic group strategies, whereas the disadvantage lays Such thematic diversity around corn and ethanol production indicates NCGA coordinates a national supply chain of significant economic relevance. In this sense, the appeal to seek new energy matrixes makes the ethanol issue critical for specific interests of the sector to be consensually seen as a U.S. national strategic interest.…”
Section: Us Domestic Policy Formulationmentioning
confidence: 99%
“…On the basis of these previous studies, Putnam [18], Mayer [15], and Lehman and McCoy [14] have developed research on the interactions of negotiation. In his work, "Side-Payments versus Security Cards: Domestic Bargaining Tactics in International Economic Negotiations," Fridman [3] suggested that bargaining tactics with sidepayments and the redefinition of the case can make domestic support and international economic negotiation much easier than it was previously.…”
Section: Literature Reviewmentioning
confidence: 99%